Migrating foreign body into the common carotid artery and internal jugular vein - Tang, I.P; Singh, S.; Shoba, N.; Rahmat, O.; Shivalingam, S.; Gopala, K.G; Khairuzzana, B. (Auris Nasus Larynx, 2009)
Ingested foreign bodies are a fairly common otorhinolaryngological emergencies encountered in Malaysia. The vast majority of these foreign bodies are fish bones which most commonly are impacted at the level of the cricopharynx. Rarely, however, a foreign body may migrate extraluminally and may even extrude subcutaneously. We report a rare occurrence where a fish bone not only migrated extraluminally, it was found to have migrated into the common carotid artery and the internal jugular vein and required surgical removal.